2004
DOI: 10.1515/cclm.2004.130
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for the production of multicentre physiological reference values using the same measurement system. A proposal of the Catalan Association for Clinical Laboratory Sciences

Abstract: This article is intended as a guide for the production of biological reference values of healthy people (physiological reference values) by several clinical laboratories using the same measurement system. This guide is a proposal from the Catalan Association of Clinical Laboratory Sciences to be applied worldwide at a regional level. This guide makes it possible for all clinical laboratories in a region using the same measurement system to adopt the same physiological reference limits. The model presented here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This way of thinking seems too conceptual for clinicians; for him/her, the cut-off value (decision limit) alone will be taken into account. 6. We are quite far away from the recommendation of the IFCC (95% reference intervals).…”
Section: The Concept Of Reference Values Is Not Used By Laboratory Scmentioning
confidence: 90%
See 2 more Smart Citations
“…This way of thinking seems too conceptual for clinicians; for him/her, the cut-off value (decision limit) alone will be taken into account. 6. We are quite far away from the recommendation of the IFCC (95% reference intervals).…”
Section: The Concept Of Reference Values Is Not Used By Laboratory Scmentioning
confidence: 90%
“…There are, however, strong arguments in favor of such a publication. In this issue, Fuentes-Arderiu et al suggest techniques for determining multicenter reference values (6). Some laboratory scientists are publishing interesting scientific papers without following the official recommendation of Scientific Bodies using the desirable rigor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind all of the above, the aims of this work were (i) to establish physiological reference limits for the concentration of creatininium in plasma using a multicentre approach (8), and (ii) to evaluate the specificity of the glomerular filtration rate estimated with the four-variable MDRD Study equation when applied to healthy persons to screen for chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…The production of common RIs for homogeneous populations shared by all laboratories within a country or a region has attracted a lot of interest. In Spain, the Catalan Association for Clinical Laboratory Science has demonstrated that it is possible to establish common RIs for an entire country for laboratories using the same equipment and reagents, with ensured metrological traceability [ 5 ]. Almost simultaneously, a Nordic European Group proposed a new concept of shared reference values based on the recommendations of the IFCC-LM, but specifying prerequisites [ 6 ].…”
mentioning
confidence: 99%